Pengaruh Keaktifan di Organisasi Kemahasiswaan Terhadap Soft Skills Dan Kesiapan Menjadi Calon Guru Bagi Mahasiswa Pendidikan Agama Islam Unsiq Wonosobo - Ngabdur Rosyid; Nurul Mubin; Ahmad Robihan (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This study aims to analyze the effect of activeness in student organizations on soft skills and readiness to become prospective teachers for Islamic Religious Education (PAI) students of Al-Qur’an Sains University (UNSIQ) Wonosobo. This study uses a quantitative method with an ex post facto research design. Data collection techniques were carried out through questionnaires distributed to 40 PAI UNSIQ students who were active in student organizations. Data were analyzed using simple linear regression techniques and t-tests. The results of the study showed that there was a positive and significant effect between activeness in student organizations on soft skills of PAI UNSIQ students (rxy1 = 0.593, p < 0.05). This finding also shows that there is a positive and significant effect between activeness in student organizations on readiness to become prospective teachers of PAI UNSIQ students (rxy2 = 0.593, p < 0.05). The conclusion of this study is that activeness in student organizations has a positive and significant effect on soft skills and readiness to become prospective teachers for PAI UNSIQ Wonosobo students. Activeness in organizations provides various benefits for students, such as improving communication skills, leadership, teamwork, and problem solving, which are important soft skills for prospective teachers to have in facing various challenges in the future.